Warring Claims: Victorian Poetry and Conflict - Matthew Bevis (Cahiers Victoriens et Edouardiens)
The First World War is often seen as heralding a break between Victorian and modern conceptions of conflict, and critics have tended to opt for a series of neat poetic oppositions—the glorious versus the gruesome, the heroic versus the hellish, the romantic versus the realistic. One need not deny the differences between writing before and after the First World War without feeling that such oppositions do a disservice to the complexities of both nineteenth- and twentieth-century war poetry, to the former in particular. Victorian war poetry has frequently been belittled or ignored by critics, usually by way of dismissive references to Tennyson serving as prelude to discussion of the poets of the Great War. Even Malvern Van Wyk Smith, in what remains the only book-length study of the subject, confines himself to the Anglo-Boer War and closes with the assertion that “after the Boer War, war poetry could no longer be merely a sub-department of patriotic verse.” But war poetry was not “merely” this before the Boer War. This article examines how Victorian poets represented and explored the complexities of war; it considers the writings of Browning, Arnold, Tennyson, Meredith, Morris, Kipling, Hardy, Housman, and others, and demonstrates how the richness of this body of work offered itself to modern poets as both bequest and as monitory force.